An Observationa Study on the Role of Zinc Sulphate in Paracetamol Toxicity - Muhammad Afzal, Saeed Akbar Tariq, Bilal Ahmad, Rashid Mahmood Khan, Muaaz Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The aim of this study was to determine the role of Zinc Sulphate as an agent of hepatoprotective in the acetaminophen-induced changes of histopathological nature in the model of animals. Methodology: The design of this study was observational study design. This study was conducted at Allied Hospital Faisalabad and the duration of this study was from April 2022 to July 2022. Our research sample was 90 albino rats with the range of weight from 18 – 32 grams and we made three groups each group consisting of thirty albino rats. Control group was A group and normal saline level was maintained in this group as 0.9%; acetaminophen was given (250 mg / kg) in B group through a single dose; Zinc Sulphate (1 – 5 mg / kg) was given to C group for a duration of 1 – 7 days before the acetaminophen (250 mg / kg) Sigle dose. After the six hours’ duration was conducted biochemical studies after giving acetaminophen to albino rats. At last step of the treatment weight of all animals was checked at than sacrificed. Histopathological and gross examination was carried out for liver and statistical evaluation of the data was carried out through Chi-Square test. Results: Demonstration of the zinc’s protective effect was made through serum concentration reduction level of the enzymes of liver such as aspartate aminotransferase, lactate dehydrogenase, alanine aminotransferase and serum sorbitol dehydrogenase, including the histopathological centrilobular congestion changes, necrosis and hepatocellular degeneration. We observed through the histopathological evaluation that typical changes in pathological environment of centri-zonal necrosis, leukocyte infiltration, steatosis, edema in animals and portal tiraditos those were treated only with acetaminophen. Animal pretreatment through zinc sulphate lead the whole procedure to dependent on the dose for the avoidance of various changes. Practical Implication: In the practical implication of this study the determination of the Zinc Sulphate role as an agent of hepatoprotective in the acetaminophen-induced changes of histopathological nature in the model of animals. Conclusion: It is concluded that Zinc is responsible for the production of hepato-protective effect with the prevention of ultrastructural hepatic tissue injuries and also causes free amino acid metabolism disturbance which is a result of the acetaminophen toxic dose. Keywords: Acetaminophen, Zinc, Liver Toxicity And Hepato-Protective Effect.